2017
DOI: 10.1002/2016jb013582
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the oceanic lithosphere and upper mantle north of the Gloria Fault in the eastern mid‐Atlantic by receiver function analysis

Abstract: Receiver functions (RF) have been used for several decades to study structures beneath seismic stations. Although most available stations are deployed on shore, the number of ocean bottom station (OBS) experiments has increased in recent years. Almost all OBSs have to deal with higher noise levels and a limited deployment time (∼1 year), resulting in a small number of usable records of teleseismic earthquakes. Here we use OBSs deployed as midaperture array in the deep ocean (4.5–5.5 km water depth) of the east… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 125 publications
(210 reference statements)
3
46
0
Order By: Relevance
“…The parameters used in the processing and comparison of results with other methods are detailed in Supplementary Discussion 4. The final group calculated RFs by using a time-domain Wiener filter that transforms the complex P wavetrain on the Z component into a band-limited spike 58,59 . This Wiener filter was applied to all three components of the seismogram to produce the RFs.…”
Section: Methodsmentioning
confidence: 99%
“…The parameters used in the processing and comparison of results with other methods are detailed in Supplementary Discussion 4. The final group calculated RFs by using a time-domain Wiener filter that transforms the complex P wavetrain on the Z component into a band-limited spike 58,59 . This Wiener filter was applied to all three components of the seismogram to produce the RFs.…”
Section: Methodsmentioning
confidence: 99%
“…The influence of uncertainties in the measured azimuth on Mars on the results is discussed below. For both data sets, the vertical component is deconvolved from the vertical and radial components in the time domain using a Wiener filter to obtain the receiver functions, as discussed in detail by Hannemann et al (2017).…”
Section: Receiver Function Calculationmentioning
confidence: 99%
“…After adjusting the method to the boundary conditions at the ocean bottom, Hannemann et al (2016) successfully applied it to an OBS data set with one to five receiver functions per station, thus demonstrating its usefulness when only a small number of event recordings is available. It has also been shown that a priori S-velocity information deduced from P-wave polarization measurements can be useful when attempting to model or invert the actual receiver function waveforms (Peng et al 2012;Hannemann et al 2017), even when polarization information at long periods is missing (Kieling et al 2011). Schiffer et al (2015Schiffer et al ( , 2016 used the frequency-dependent apparent S-wave velocities as stabilizing information in a joint inversion with receiver function waveforms, whereas Chong et al (2018) directly inverted the measured receiver function amplitude ratios instead.…”
Section: Introductionmentioning
confidence: 99%
“…We acknowledge all institutions providing seismic data used in this research: Deep Ocean Test Array (DOCTAR) project (Hannemann et al, , , ), FCT project WILAS‐West Iberia Lithosphere and Asthenosphere Structure (doi:10.14470/3n7565750319), Instituto Português do Mar e da Atmosfera (IPMA) Seismic Network, University of Lisbon Seismic Network and Western Mediterranean Seismic Network (doi:10.14470/JZ581150). DOCTAR and WILAS waveform data were accessed through the ORFEUS data center.…”
Section: Acknowledgmentsmentioning
confidence: 99%